Revealing AES Encryption Device Key on 328P Microcontrollers with Differential Power Analysis - Septafiansyah Dwi Putra; Adang Suwandi Ahmad; Sarwono Sutikno; Yusuf Kurniawan; Arwin Datumaya Wahyudi Sumari (Institute of Advanced Engineering and Science, 2018)
This research demonstrates the revealing of an advanced encryption standard (AES) encryption device key. The encryption device is applied to an ATMEGA328P microcontroller. The said microcontroller is a device commonly used in internet of things (IoT). We measured power consumption when the encryption process is taking place. The message sent to the encryption device is randomly generated, but the key used has a fixed value. The novelty of this research is the creation of a systematic and optimal circuit in carrying the differential power analysis or difference of means (DPA/DoM) technique, so the technique can be applied in key revealing on a microcontroller device by using 500 traces in 120 seconds.